Die historische Dynamik des Kapitalismus und linke Strategien: Zu Alex Demirovi? Anmerkungen über den Gebrauchswert einer Kritik der Politik - Schlemermeyer, Jan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
As an answer to Alex Demirovic’s contribution this article argues that politics should rather be conceived as a social logic, an alienated form of rationality, which is necessarily bound to the overwhelming, historical dynamic of capitalism. This point also generates important implications for an analysis of the possibilities and constraints of a progressive practice, since it exceeds the traditional critique of class domination. Although there are (of course) crucial differences between different forms of the institutionalization of state power, and they do depend upon the balance of power in a society to a certain degree, even the most progressive form of political regulation is limited by the structural constraints of capitalist accumulation. Hence, the Left should search for alternative institutional forms and aim for a decomposition of the state rather than focusing too much on questions of an intrinsic political reform of capitalism.